2022
DOI: 10.1108/k-06-2022-0852
|View full text |Cite
|
Sign up to set email alerts
|

The effects of military expenditures on labor productivity, innovation and economic growth for the most militarized countries: panel data analysis

Abstract: PurposeThere is extensive literature on the effect of military expenditure on economic growth. However, there is also a wide gap in the literature on the relationship between productivity and innovation, which is considered the driving force of economic growth and military expenditures. To this end, this study examines the effect of military expenditures on economic growth, innovation and labor productivity for the period 1995–2019 in most militarized countries.Design/methodology/approachThe tests used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Specifically, a one-unit increase in military spending leads to a 4.48% increase in GDP growth, controlling for relevant economic and demographic factors. A recent study conducted by Brigzalová et al (2022), Inal et al (2022), and Yildirim and Öcal (2016 also examined the relationship between military expenditure and economic prosperity in European countries, including Croatia. While their study found a positive correlation between military spending and GDP growth, the effect size was smaller compared to the results of the given study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a one-unit increase in military spending leads to a 4.48% increase in GDP growth, controlling for relevant economic and demographic factors. A recent study conducted by Brigzalová et al (2022), Inal et al (2022), and Yildirim and Öcal (2016 also examined the relationship between military expenditure and economic prosperity in European countries, including Croatia. While their study found a positive correlation between military spending and GDP growth, the effect size was smaller compared to the results of the given study.…”
Section: Discussionmentioning
confidence: 99%
“…A panel study by Inal et al (2022) found that there was a long-run relationship between military expenditures and productivity, innovation, and economic growth in most militarised countries. Nugroho and Purwanti (2021) stated that military expenditure did not significantly influence the economic growth, but it had a positive and significant influence when interacting with other variables.…”
Section: The Relationship Between Military Expenditure and Economic P...mentioning
confidence: 99%
“…18,25 Their argument is that defense expenditures lead to technological innovation and advancements, particularly in areas like aerospace communications and logistics. 48 This boosting affect can benefit civilian sectors and accelerate overall productivity gains. Furthermore, supporters of this claim highlight the economic benefits associated with an advancing defense industry, which may influence job creation, high-skilled employment, and export opportunities, all of which can have positive multiplier effects on the economy in terms of productivity.…”
Section: Theoretical and Modeling Backgroundmentioning
confidence: 99%
“…Moreover, although there exist different theories regarding the impact of military spending on productivity, only a limited number of studies have been conducted to empirically investigate these variables. 48…”
Section: Theoretical and Modeling Backgroundmentioning
confidence: 99%
“…His causality test results also revealed a bi-directional causality between military expenses and economic growth. Inal et al (2022) used panel cointegration tests to determine the long-run relationship between military expenditures, economic growth, innovation, and labor productivity in countries characterized by Startextensive militarization. Their study concluded that there is a long-run and causal relationship between military spending and the utilized variables.…”
Section: Literature Reviewmentioning
confidence: 99%